Kajian Pengaruh COVID-19 Terhadap Stabilitas Ekonomi Kota Mojokerto Bulan Januari - Maret 2020 - Penangsang, Parikesit; Studiviany, Pramita; Wiwoho, Bambang (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2020)
The 2019-2020 Corona virus pandemic (Covid-19) is the 2019 corona virus spread throughout the world. The Covid-19 outbreak was first detected in Wuhan City, China in December 2019, and was designated as a pandemic by the World Health Organization (WHO) on March 11, 2020. The Covid-19 outbreak resulted in Indonesia, the spread of the Corona virus not only disrupted human health, this virus also disturbs the health of the economy throughout the world.Indonesia's economic growth is expected to fall to 2.3 percent, even reaching negative 0.4 percent. The rupiah is currently touching Rp. 16,000, and has an impact on the wheels of the economy in Indonesia. Many residents of the city of Mojokerto are starting to struggle economically, buying daily necessities, is this the people's purchasing power? Public purchasing power is usually associated with rising prices in general, namely